Using the rating of perceived exertion and heart rate to quantify training intensity in female soccer players: validity and utility - Costa, J. A.; Brito, J.; Nakamura, F. Y.; Figueiredo, P.; Rebelo, A. (The Journal of Strength and Conditioning Research, 2022)
The aims of this study were as follows: (a) to analyze associations between session rating of perceived exertion (sRPE) and training impulse (TRIMP); (b) to verify whether significantly different ranges of percentage of heart rate peak (%HRpeak) would be reached in each discrete RPE category; and (c) to investigate the amount of time spent >90% of HRpeak and associated intraplayer and interplayer variability during soccer technical training sessions with similar contents and duration. This was a single-group observational study that measured the internal training load during 6 weeks of the competitive period in 17 high-level female soccer players. All training sessions started around 9 pm. and lasted on average 94 ± 5 minutes. During each training session, RPE, sRPE, TRIMP, HRex (%HRpeak), and time spent at >90% of HRpeak were assessed. A very large correlation was found between sRPE and TRIMP (r = 0.78; 95% confidence interval: [0.74-0.82]). Significant differences were observed between %HRpeak associated with each RPE value (i.e., RPE = 2 arbitrary unit [68%; 65-69% of %HRpeak]; RPE 3 [72%; 69-75%]; RPE 4 [79%; 76-82%]; RPE 5 [84; 81-87%]; Chi2 = 73.34; df = 3; P < 0.001). Intraplayer and interplayer coefficients of variation for the time spent >90% of HRpeak (~8% of training time, ~7 minutes per session) during training sessions were 73 and 92%, respectively. In conclusion, it was confirmed that sRPE and TRIMP displayed good convergent validity, and different %HRpeak were observed for each discrete RPE. However, because of the high variability in the time >90% of HRpeak, careful monitoring of individual exercises should be performed to ensure the desired training stimulus for each player.